Pulmonary hypertension and heart failure: alternative indexes of right ventricular-pulmonary artery coupling - V. A. Mareyeva; A. A. Klimenko; N. A. Shostak (Столичная издательская компания, 2023)
Pulmonary hypertension is a serious cardiovascular pathology, often complicating the course of heart failure (HF). Excessive pulmonary artery pressure increases right ventricular afterload and progressively leads to dysfunction, which is associated with adverse outcomes regardless of left ventricular ejection fraction. In this regard, more attention should be paid to determining the right ventricular condition. Currently, in order to assess the right heart function in patients with pulmonary hypertension and HF, the right ventricular (RV)-pulmonary arterial (PA) coupling, is increasingly being used. The conventional formula to calculate this parameter is the ratio of tricuspid annular plane systolic excursion (TAPSE) and pulmonary artery systolic pressure (PASP). This index has proven to be a powerful predictor of adverse outcomes. But this calculation method has a number of limitations and can lead to errors. It is extremely important to exclude or minimize any possible inaccuracies during prognostic assessment, which is why new researches of alternative RV-PA calculation options have been recently published. Such things as problems that can occur during TAPSE and PASP evaluation, ways of modifying the assessment of right heart's functioning in patients with pulmonary hypertension and heart failure have been addressed. The value of new RV-PA alternative «surrogate» indexes has been discussed.